Behavioral Biases in Corporate Tax Compliance in Indonesia: The Moderating Role of Culture and Digital Technology - Dewantara, Bachtiar; Nugraha; Disman; Sari, Maya; Ramdhany, Muhamad Arief (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to analyze the effects of various behavioral biases on corporate tax compliance in Indonesia and examine the moderating roles of cultural variation and digital technology. A quantitative approach was used, with data collected through a questionnaire distributed to 384 corporate taxpayers across Indonesia using proportional random sampling. The analysis was conducted using Partial Least Squares (PLS) and moderation regression techniques. The results show that optimism bias and fairness perception significantly influence corporate tax compliance, while status quo bias, heuristic bias, and framing effect do not. Cultural variation and digital technology moderate the effects of certain behavioral biases, highlighting the role of social and digital contexts in shaping tax-related decisions. These findings suggest that taxpayer behavior is not solely rational but also influenced by psychological and contextual factors. The study offers theoretical insights by integrating behavioral economics with contextual moderators in tax compliance behavior. Practically, it suggests that tax authorities should leverage behavioral insights and digital technologies to enhance compliance strategies. This research uniquely contributes by examining the intersection of behavioral biases, cultural variation, and digital technology in the context of corporate tax compliance in Indonesia.